Obesity Among Female Adolescents Of Tehran Schools - Masumeh Shakeri; Yusef Mojtahedi; Javad naserian; Maryam Moradkhani (Tehran University of Medical Sciences, 2013)
Background and Aim: Obesity in childhood can cause obesity and its related complications in adulthood. This study was aimed to determine the correlateion between obesity among female adolescents and its related complications of Tehran schools in 2011. Materials and Methods: In this cross-sectional study, 810 female adolescents, aged 12-16 years old, studying in schools of Tehran University of Medical Sciences were selected using multi-stage random sampling. Height and weight of the participants were measured and their BMI calculated. Data were collected using a questionnaire. Validity and reliability of the questionnaire was confirmed using content validity and test-retest. Using BMI, the participants were categorized into obese(BMI>95 percentile for age and gender) and overweight(BMI between 85 and 95 percentiles for age and gender) individuals. Data were analyzed using the Chi-squared test, Fisher's exact test, ANOVA, and multivariate logistic analysis. Results: The prevalence of overweight and obesity in our study were 4.4%(95% CI 4/2-6/4) and 14/1%(95% CI 10/25-15/3), respectively. There was a statistically significant relationship between obesity and TV watching(p<0.001). Conclusion: Based on our findings, further investigations are recommended to determine factors affecting overweight.